Characterization and rhizosphere competence of Trichoderma spp. in different cropping systems of Chitoor district (A.P.) - A.K. PATIBANDA; R. SARADA JAYALAKSMHI DEVI, A. RANGA RANI, S. KHAYUM AHAMMED* (Indian Phytopathology, 2016)
Nine isolates of Trichoderma were isolated from different cropping systems (Groundnut, Tomato and Redgram) of Chittoor district (A.P) and were characterized based on growth rate, GRT-2, GRT-3, RRT-2 and TRT-2 were categorized as very fast growing; GRT-1, RRT-1 and TRT-1 as fast growing and GRT-4, GRT-5 as medium growing. In dual culture GRT-3 found as best antagonist against A. niger (Incitant of collar rot in groundnut) and F. oxysporum (Incitant of wilt in redgram). In case of rhizosphere colonization of GRT-3 in groundnut, redgram and tomato crops found as best upto 15 days after sowing. Highest rhizospheric colonization was found in redgram plant, i.e. 28 and 35 x 108 cfu/g of soil in both natural and autoclaved soil respectively followed by tomato and groundnut.